Psychological distress and associated factors among the attendees of traditional healing practices in Jinja and Iganga districts, Eastern Uganda: a cross-sectional study - Abbo, Catherine; Ekblad, Solvig; Waako, Paul; Okello, Elialilia; Muhwezi, Wilson; Musisi, Seggane (International Journal of Mental Health Systems, 2008)
Mental health problems are a major public health concern worldwide. Evidence shows that African communities, including Uganda, use both modern and traditional healing systems. There is limited literature about the magnitude of psychological distress and associated factors among attendees of traditional healing practices. This study aimed to determine the prevalence and associated factors of psychological distress among attendees of traditional healing practices in two districts in Uganda.
Keywords: Psychological distress; Attendees; Traditional healing practices; Eastern Uganda